Muslim Women at Work Religious Discourses in Arab Society - Sidani, Yusuf M. (Springer International Publishing, 2018)
This book explores how a growing religious discourse is advocating for change in women's employment participation in Arab societies. It provides a historical and cultural overview of women in Arab societies as well as issues of homogeneity and heterogeneity in religion. An emerging group of activists, intellectuals, and religious scholars are rocking the boat of traditional Islamic understanding of the role of women and their economic and social participation, which is rooted in reinterpretations of the religious texts and history. Signs of this change are already seen in some Arab workplaces though with varying degrees of success. This book uncovers a neglected discourse on the status of Arab women that is relevant to students and academics with interest in economics, gender studies, the Middle East, and Islam. .